FOREIGN AND INSTITUTIONAL OWNERSHIP AND FINANCIAL STATEMENT FRAUD AMONG NON-FINANCIAL LISTED FIRMS ON THE NIGERIA EXCHANGE GROUP (Journal of Global Accounting, 2023)
This work examines the influence of foreign and institution ownership on financial statement fraud among non-financial listed firms in Nigeria. The high rates of business failure are linked with financial statement fraud; hence this study tends to examine the influence of foreign and institution ownership on the financial statement fraud among selected listed manufacturing firms in Nigeria. The objective of this study is to examine the influence of foreign and institution ownerships on financial statement fraud among non-financial listed firms on Nigerian Exchange Group. The study used an ex post facto research design. Ninety-five (95) non-financial firms listed as at 31st December 2022. The study used a purposive sampling technique to select the sample size from the population. The study adopted secondary source of data. Ordinary Least Square multiple regression and Binary Logit Regression Technique were used to analyze the data collected for this work through the aid of E-View 9.0 software. The findings of the study revealed that foreign and institutional ownerships have significant effects on the financial statement fraud among non-financial listed firms in Nigeria. Based on the results and analysis, this study concludes that foreign and institutional ownerships have significant effect on the financial statement fraud of non-financial firms listed on the Nigerian Exchange Group (NGX). This study recommended among others based on the findings of this study since foreign and institutional ownership have significant effects on financial statement fraud, regulatory authorities like Financial Reporting Council of Nigeria and Nigeria Exchange Group (NGX) should make policy that will encourage foreign investors to own more shares in non-financial listed firms because foreign ownership will demand management to be transparent in financial reporting to maximize control and minimize fraudulent actions.
Keywords: Foreign Ownership; Institutional Ownership; Financial Statement Fraud; listed non-financial firms